Anti-inflammatory Activity Of Some Novel α-Amino Naphthalene Derivatives - Sharma, Shalabh; Srivastava, Virendra Kishore; Kumar, Ashok (Arzneimittelforschung, 2003)
α-Acetylamino naphthalene (1) was reacted with different aromatic aldehydes and with primary or secondary amines to give α-aminonaphthylsubstitutedaryl chalkones (2–5) and α-(substituted aminoethyl)-amidonaphthalenes (14–25), respectively. These substituted chalkones were treated with hydrazinehydrate and hydroxylamine hydrochloride to give 1-acetyl-5-substitutedaryl-3-(α-aminonaphthyl)-2-pyrazolines (6–9) and α-(2-substitutedaryl-isoxazolin-4-yl)-aminonaphthalenes (10–13), respectively. Their chemical structures were confirmed by IR and 1H-NMR spectral data and ele-mental analysis. Studies of the anti-inflammatory and ulcerogenic activities and acute toxicity of these newly synthesized compounds were performed in vivo and compared with the standard drug, phenylbutazone (CAS 50-33-9). Some of these compounds showed potent anti-inflammatory activity and less ulcerogenic effects than phenylbutazone.
Keywords: Amidonaphthalenes, anti-inflammatory and ulcerogenic activities, rat, substituted,; synthesis, toxicity study; α-Aminonaphthyl substituted aryl chalkones, anti-inflammatory and; ulcerogenic activities, rat, synthesis, toxicity study; Isoxazolines; Pyrazolines